Coupling coordination and spatiotemporal dynamic evolution between culture and tourism industry in Japan - Yiming Liu; Yuting Xue; Haoxiang Zhao; Haikang Yao; Xinyue Zhan; Sunhee Suk; Liguo Wang; Yuan Yuan (Scientific Reports)
Abstract In order to adapt to the needs of tourism industry transformation and tourism product upgrades, it is increasingly urgent to deeply research the relationship between culture and tourism. This study examines the integrated development level of the cultural and tourism industry in the spatial and temporal dimensions based on the coupling coordination degree, using data on the industry in 46 prefectures in Japan from 2009 to 2019. It also uses spatial kernel density estimation and spatial cluster analysis methods to gain insight into the patterns of spatial association between the industry and its data. The following two points were found: (1) From the time perspective, while the development of other regions has been rather stable, Tokyo and Osaka have demonstrated a particularly notable rising tendency in the total development level of Japan’s culture and tourism industry. Moreover, the relationship between culture and tourism industry has strengthened over time, showing a positive development trend overall, and the spatial distribution shows an unbalanced development pattern of high in the middle and low on both sides; (2) From the perspective of spatial correlation pattern, Japan’s cultural and tourism industry exhibits a notable positive spatial agglomeration pattern, particularly in economically advanced regions like Tokyo and Osaka, indicating a high level of concentration. Certain distant regions in the northern and southern parts exhibit a low-low agglomeration pattern.